2011
DOI: 10.1016/j.jcin.2011.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Periprocedural and Short-Term Outcomes of Transfemoral Transcatheter Aortic Valve Implantation With the Sapien XT as Compared With the Edwards Sapien Valve

Abstract: The new SXT valve has the same short-term performance as the ESV but seems to be associated with a lower risk of major vascular complications and thus has a broader clinical application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 18 publications
5
45
0
1
Order By: Relevance
“…[8][9][10][11][12][13][14][15][16][17]21,24,25 This may reflect differences in our population compared with the entire Pivotal Trial cohort or the general population post approval or perhaps a broader indication. The rate of high-grade AV block (complete heart block or Mobitz II second-degree block) was 22.9%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11][12][13][14][15][16][17]21,24,25 This may reflect differences in our population compared with the entire Pivotal Trial cohort or the general population post approval or perhaps a broader indication. The rate of high-grade AV block (complete heart block or Mobitz II second-degree block) was 22.9%.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found a PPI rate of 18-34% for the CoreValve' versus 4-12% for the SAPIEN' valve (Edwards Lifesciences, Irvine, CA). [9][10][11][12][13][14][15][16][17] Additionally, the CoreValve' has been associated with a higher incidence of procedural related left bundle branch block (LBBB) than the SAPIEN'. [16][17][18][19][20] It is not yet fully understood what causes these marked differences.…”
Section: Introductionmentioning
confidence: 99%
“…5,6,26,30,56,57 To reduce the risk of vascular complications, alternative access routes have been proposed (ie, the transapical approach, the transaortic, the subclavian, the transaxillary, the transcarotid, and the retroperitoneal access) which can be considered in patients with an unfavorable iliofemoral anatomy. [58][59][60][61][62] In addition, effort has been made to miniaturize the delivery systems and develop valves with a low crossing profile.…”
Section: Vascular Complicationsmentioning
confidence: 99%
“…45 Istraaeivanje kod 120 bolesnika je pokazalo da je postignut kratkoroËni uËinak kao i s prethodnom SAPIEN valvulom, ali je bila povezano s tri puta manjim rizikom od velikih vaskularnih komplikacija. 46 Istraaeivanje PARTNER je bila prva prospektivna randomizirana kontrolirana studija za TAVR u svijetu. Bile su formirane su dvije skupine:…”
Section: Aortic Valve Interventionsunclassified
“…45 A trial on 120 patients showed that it had the same short term performance as the earlier SAPIEN valve but was associated with threefold lower risk of major vascular complications. 46 The PARTNER valve trial was the world's first prospective randomised controlled trial for TAVR. It was designed with two arms:…”
Section: Aortic Valve Interventionsmentioning
confidence: 99%